Highway safety manual. (American Association of State Highway and Transportation Officials, 2010)
"The Highway Safety Manual (HSM) is a resource that provides safety knowledge and tools in a useful form to facilitate improved decision making based on safety performance. The focus of the HSM is to provide quantitative information for decision making. The HSM assembles currently available information and methodologies on measuring, estimating and evaluating roadways in terms of crash frequency (number of crashes per year) and crash severity (level of injuries due to crashes). The HSM presents tools and methodologies for consideration of 'safety' across the range of highway activities: planning, programming, project development, construction, operations, and maintenance. The purpose of this is to convey present knowledge regarding highway safety information for use by a broad array of transportation professionals"--Page xxiii.
Keywords: Traffic safety -- United States -- Handbooks, manuals, etc.; Roads -- United States -- Safety measures -- Handbooks, manuals, etc.; elektronické knihy; electronic books